हिंदी

Let F ( X ) { a X 2 + 1 , X > 1 X + 1 / 2 , X ≤ 1 . Then, F (X) is Derivable at X = 1, If (A) a = 2 (B) a = 1 (C) a = 0 (D) a = 1/2 - Mathematics

Advertisements
Advertisements

प्रश्न

Let \[f\left( x \right)\begin{cases}a x^2 + 1, & x > 1 \\ x + 1/2, & x \leq 1\end{cases}\] . Then, f (x) is derivable at x = 1, if 

विकल्प

  • a = 2

  • a = 1

  • a = 0

  • a = 1/2

MCQ

उत्तर

(d) a = 1/2 

Given:  

`f(x) = {(ax^2 +1 , x>1),(x +1/2, xle 1):}`

The function is derivable at x = 1, iff left hand derivative and right hand derivative of the function are equal at x = 1.

\[\left( \text { LHD at x } = 1 \right) = \lim_{x \to 1^-} \frac{f\left( x \right) - f\left( 1 \right)}{x - 1}\]
\[\left( \text { LHD at x } = 1 \right) = \lim_{h \to 0} \frac{f\left( 1 - h \right) - f\left( 1 \right)}{1 - h - 1}\]
\[\left( \text { LHD at x } = 1 \right) = \lim_{h \to 0} \frac{f\left( 1 - h \right) - f\left( 1 \right)}{- h}\]
\[\left( \text { LHD at x = 1 } \right) = \lim_{h \to 0} \frac{\left( 1 - h + \frac{1}{2} \right) - \frac{3}{2}}{- h} = 1\]
\[\left( \text { RHD at x = 1 } \right) = \lim_{x \to 1^+} \frac{f\left( x \right) - f\left( 1 \right)}{x - 1}\]
\[\left( \text { RHD at x = 1 } \right) = \lim_{h \to 0} \frac{f\left( 1 + h \right) - f\left( 1 \right)}{1 + h - 1}\]
\[\left( \text { RHD at x = 1 } \right) = \lim_{h \to 0} \frac{f\left( 1 + h \right) - f\left( 1 \right)}{h}\]
\[\left( \text { RHD at x = 1 } \right) = \lim_{h \to 0} \frac{a \left( 1 + h \right)^2 + 1 - \frac{3}{2}}{h}\]
\[\left( \text { RHD at x } = 1 \right) = \lim_{h \to 0} \frac{a\left( 1 + h^2 + 2h \right) - \frac{1}{2}}{h}\]
\[ \because\text {  LHD = RHD }\]
\[ \Rightarrow a - \frac{1}{2} = 0\]
\[ \Rightarrow a = \frac{1}{2}\]

shaalaa.com
  क्या इस प्रश्न या उत्तर में कोई त्रुटि है?
अध्याय 10: Differentiability - Exercise 10.4 [पृष्ठ १८]

APPEARS IN

आरडी शर्मा Mathematics [English] Class 12
अध्याय 10 Differentiability
Exercise 10.4 | Q 15 | पृष्ठ १८

संबंधित प्रश्न

If xpyq = (x + y)p+q then Prove that `dy/dx = y/x`


Find dy/dx if x sin y + y sin x = 0.


Find  `dy/dx` in the following:

2x + 3y = sin x


Is |sin x| differentiable? What about cos |x|?


Find `(dy)/(dx)` if `y = sin^-1(sqrt(1-x^2))`


Differentiate tan-1 (cot 2x) w.r.t.x.


Find `"dy"/"dx"` if x = at2, y = 2at.


Find `"dy"/"dx"`, if : x = `sqrt(a^2 + m^2), y = log(a^2 + m^2)`


Find `"dy"/"dx"`, if : x = a(1 – cosθ), y = b(θ – sinθ)


Find `"dy"/"dx"` if : x = t2 + t + 1, y = `sin((pit)/2) + cos((pit)/2) "at"  t = 1`


Differentiate `cos^-1((1 - x^2)/(1 + x^2)) w.r.t. tan^-1 x.`


Find `(d^2y)/(dx^2)` of the following : x = sinθ, y = sin3θ at θ = `pi/(2)`


If x = at2 and y = 2at, then show that `xy(d^2y)/(dx^2) + a` = 0.


If y = `e^(mtan^-1x)`, show that `(1 + x^2)(d^2y)/(dx^2) + (2x - m)"dy"/"dx"` = 0.


If y = sin (m cos–1x), then show that `(1 - x^2)(d^2y)/(dx^2) - x"dy"/"dx" + m^2y` = 0.


If x2 + 6xy + y2 = 10, show that `(d^2y)/(dx^2) = (80)/(3x + y)^3`.


If x = a sin t – b cos t, y = a cos t + b sin t, show that `(d^2y)/(dx^2) = -(x^2 + y^2)/(y^3)`.


Choose the correct option from the given alternatives :

If y = `a cos (logx) and "A"(d^2y)/(dx^2) + "B""dy"/"dx" + "C"` = 0, then the values of A, B, C are


Differentiate the following w.r.t. x : `tan^-1((sqrt(x)(3 - x))/(1 - 3x))`


If `x = e^(x/y)`, then show that `"dy"/"dx" = (x - y)/(xlogx)`


Find `"dy"/"dx" if, sqrt"x" + sqrt"y" = sqrt"a"`


Find `"dy"/"dx"` if, x3 + x2y + xy2 + y3 = 81


Find `"dy"/"dx"` if, yex + xey = 1 


Find `"dy"/"dx"` if, xy = log (xy)


Choose the correct alternative.

If x = `("e"^"t" + "e"^-"t")/2, "y" = ("e"^"t" - "e"^-"t")/2`  then `"dy"/"dx"` = ? 


If x2 + y2 = 1, then `(d^2x)/(dy^2)` = ______.


If `sqrt(x) + sqrt(y) = sqrt("a")`, then `("d"y)/("d"x)` is ______


Find `(dy)/(dx)`, if `y = sin^-1 ((2x)/(1 + x^2))`


Find `dy/dx if, x= e^(3t), y = e^sqrtt`


`"If" log(x+y) = log(xy)+a  "then show that", dy/dx=(-y^2)/x^2`


If log(x+y) = log(xy) + a then show that, `dy/dx = (-y^2)/x^2`


Find `dy/dx` if , x = `e^(3t), y = e^(sqrtt)`


Find `dy/dx` if, x = `e^(3t)`, y = `e^sqrtt`


Solve the following.

If log(x + y) = log(xy) + a then show that, `dy/dx = (-y^2)/x^2`


Find `dy/dx` if, `x = e^(3t), y = e^sqrtt`


If log(x + y) = log(xy) + a, then show that `dy/dx = (-y^2)/x^2`


Share
Notifications

Englishहिंदीमराठी


      Forgot password?
Use app×